MULTI-HOP WIRELESS SENSOR NETWORKS FOR REMOTE MONITORING OF SOIL MOISTURE - HELMEE, FATIN ZAFIRAH (2018)
This project was hoped to help the farmer to monitor the soil moisture effectively. In this project, a studied on developing soil moisture remote monitoring system using Wireless Sensor Network (WSN) was developed to monitor soil moisture monitoring that work in real life. WSN consists of a group of nodes that have capabilities to sense, compute data and communicate between each other to transmit the data. The motivation of this technique driven by the limitation of conventional soil moisture monitoring technique that are inaccurate data and expensive cost due to the installation and hiring manpower. WSN technology can help to minimize manpower and cost. Besides, the data can be transmitted faster and accurate to the user. In order to develop the system, IRIS XM2110 sensor nodes integrated with MDA300 data acquisition board and EC-05 soil moisture sensor used to detect temperature, humidity and soil moisture. Sensor nodes were arranged in mesh topology and transmit the monitoring data between each other to the base station. The data can be monitored anywhere by using software that connect the desktop with external devices. The number of packet drop, area network coverage and Radio Signal Strength Indicator (RSSI) were studied and analyzed. III